Toward the favorable consequences of academic motivation and L2 enjoyment for students' willingness to communicate in the second language (L2WTC) - Guihua Cao (Frontiers in Psychology, 2022)
Students' willingness to communicate in the second language (L2WTC) is perceived to be the ultimate goal of L2 acquisition in that high levels of L2WTC facilitate L2 use. For this reason, factors leading learners to higher levels of L2WTC have been widely scrutinized. Yet, the role of psycho-emotional factors like academic motivation and L2 enjoyment in promoting students' L2WTC has remained elusive. Moreover, as existing literature reveals, no inquiry has conceptually reviewed the impacts of these factors on students' L2WTC. To respond to this gap, this conceptual review strived to elucidate the consequences of academic motivation and L2 enjoyment for students' L2WTC. The favorable effects of academic motivation and L2 enjoyment on students' L2WTC levels were shown in the light of empirical and theoretical evidence. Finally, the potential implications of the findings are highlighted.